Inhibition of intestinal transit by methanolic extracts of Annona muricata L. sheets (Soursop) in mice - Salinas A, Dorka I (2011)
The leaves of soursop (Annona muricata L.) are traditionally used to treat acute diarrhea; the matter, has not found enough information to validate its property antidiarrheal, so was proposed to assess experimentally the action and acute toxicity. For that, 11 groups were formed randomly, 6 male mice Balb-C 56 each. Group one served as control (1 mL saline), the experimental groups 2, 3, 4, 5, 6 and 7 received methanol extract of Annona muricata L. in doses: 10, 25, 50, 75, 100 and 200 mg/kg body weight, respectively; the group eight received loperamide 1 mg/kg and the group nine castor oil 10 mL/kg. Activated carbon was used as a marker of intestinal transit by model in vivo in mice. The lethal dose 50 for the biological sample was 229 mg/kg, with a confidence interval of 95% (244,3 upper and lower 220,9). At doses of 25 mg/kg of Annona muricata L., a reduction of intestinal transit of 13,94% (p <0,05), similar to that given by loperamide (13,36%). We conclude that in experimental conditions the methanol extract of leaves of Annona muricata L. inhibited the intestinal transit.